Hierarchical Factors Influencing Minimum Dietary Diversity Among Children Aged 6–23 Months: A Machine Learning Approach - Devi Savitri Effendy (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Dietary diversity is an important indicator for assessing diet quality in early childhood. Minimum Dietary Diversity (MDD) is widely used to evaluate the nutritional adequacy of diets among children aged 6–23 months, in accordance with World Health Organization (WHO) recommendations. Objectives: This study aimed to identify factors associated with the achievement of MDD among children aged 6–23 months in Kendari City using a Classification and Regression Tree (CRT) approach. Methods: This was a cross-sectional study involving 123 children selected through simple random sampling. Data were collected through structured interviews and anthropometric measurements, covering maternal and child sociodemographic characteristics, child feeding practices, and continued breastfeeding status. Bivariate analysis was conducted using the chi-square test, while predictive analysis was performed using the CRT algorithm with cross-validation. Results: To showed that 62.6% of children met the MDD criteria. Chi-square analysis indicated significant associations between maternal education (p = 0.001), number of children in the household (p = 0.002), and continued breastfeeding status (p = 0.005) with MDD achievement. The CRT model generated 15 nodes, including eight terminal nodes, with a risk estimate of 0.252 (SE = 0.039), indicating good classification performance. Maternal education emerged as the primary predictor, followed by continued breastfeeding status, child nutritional status (weight-for-age z-score), and child age. Children of highly educated mothers with good nutritional status who continued breastfeeding had the highest likelihood of achieving MDD. Conclusion: These findings highlight the importance of improving maternal nutrition literacy and supporting continued breastfeeding practices as strategies to enhance diet quality among young children at the community level.